1998
DOI: 10.4278/0890-1171-12.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions Related to Smoking among Pregnant and Postpartum Women in a Low-Income, Multiethnic Setting

Abstract: Results suggest that many women respond to warnings about smoking during pregnancy, but actions are not necessarily measured in quit rates. Misconceptions about the risks may help to rationalize continued smoking. Subjects lacked knowledge about how best to reduce the risks of passive smoke. Educational efforts may be effective when directed at networks of women who share information. The nature of qualitative data collection prevents extrapolation of these results to a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 16 publications
5
49
2
Order By: Relevance
“…8 Most pregnant women seem to worry about the negative consequences associated with the use of tobacco; however, only 30% of them try to quit smoking after becoming aware of the pregnancy. 9 Although pregnancy is a motivator to quit smoking, a recent study has shown that the percentage of pregnant women who actually quit smoking is not meaningful when compared to the general population. 10 There is a higher prevalence of cigarette consumption among depressive women than among those with no sign of depression.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most pregnant women seem to worry about the negative consequences associated with the use of tobacco; however, only 30% of them try to quit smoking after becoming aware of the pregnancy. 9 Although pregnancy is a motivator to quit smoking, a recent study has shown that the percentage of pregnant women who actually quit smoking is not meaningful when compared to the general population. 10 There is a higher prevalence of cigarette consumption among depressive women than among those with no sign of depression.…”
Section: Introductionmentioning
confidence: 99%
“…For younger women in particular, this was seen as particularly important in maintaining friendships and social standing. 123,124,129,130,136,139 Community influences supporting smoking cessation Community influences also supported women's efforts not to smoke, although less often than they supported continued smoking. In the reviews, smoking in pregnancy -and, to a lesser extent, resuming smoking post partum -aroused disapproval from some peers, particularly when the pregnancy was visible.…”
Section: Community Influences Hindering Smoking Cessationmentioning
confidence: 99%
“…HPs who were 'facilitating' were described as friendly, non-judgemental and applying a positive and systematic approach to supporting cessation. 115,116,122,123,136 In our interviews with women, there was a strong focus on the midwife or, for those who accessed cessation services, the SSS advisor. Women often described their midwife as supportive and reassuring, and they viewed this as an important and positive relationship.…”
Section: Barriers From Partners and Significant Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational efforts might be most effective when directed at networks of women who share information. 46 Although some programs did not see significant increases in postpartum relapse rates, researchers still suggested that successful relapse prevention programs should be added to cessation interventions, with increased duration and potency. 11,52 These programs should include messages aimed at bolstering confidence in being able to continue not smoking, 52 and be delivered throughout prenatal, postpartum, 48 and early childhood care.…”
Section: Interventions That Maintain Smoking Cessation During Pregnancymentioning
confidence: 99%